Fragile bones of elite cyclists: to treat or not to treat? - Hilkens, L.; Knuiman, P.; Heijboer, M.; Kempers, R.; Jeukendrup, A. E.; van Loon, L. J. C.; van Dijk, J. W. (Journal of Applied Physiology, 2021)
Accumulating evidence suggests that most elite cyclists have lower bone mineral density (BMD) values when compared with their nonelite counterparts (1) or sedentary young males (2, 3). This raises the question whether these ostensibly healthy athletes have a higher acute bone fracture risk and a higher risk of osteoporosis and associated comorbidities later later in life. Although treatment of low BMD seems warranted in elite cyclists, the benefits of treatment for health and performance in this population remain to be established. In this viewpoint, we describe the etiology and consequences of impaired bone health in elite cyclists and discuss the need for interventions to optimize bone health in this unique population.